The role of military science in the training of internal troops of the Ministry of Internal Affairs of the Republic of Kazakhstan - Zhaksylykov, Руслан (Рroblems of engineering and professional education, 2023)
Some probems of forming military acience in Interior Army of the Ministry of International Affairs of the Republic 0f Kazakhstan influencing on the training of servicemen are considered in the article